Geoecological assessment of spatial comfort of the population and bioproductivity of landscapes (regional aspect) - Matsaev Salanbek; Dzhabrailov Said-Emin; Nanaev Isa (E3S Web of Conferences, 2024)
The article presents a geoecological assessment of the spatial comfort of the population of the Chechen Republic, as well as the natural bioproductivity of landscapes. Cartographic and tabular materials on the problem of environmental safety have been compiled. The main ecological problem of the Republic on the reduction of productive lands per capita is indicated. Conclusions and recommendations are made on the rational use and sustainability of landscape complexes, for planning and housing of the population, and industries of farms.